Fluid Evolution through Different Deformation Stages: A carbonate outcrop-based study in the Western Highland of Thailand - Nazrul Liaw, Mohammad (Bulletin of Earth Sciences of Thailand, 2021)
Veins offer the opportunity to study the burial and thermal evolution of rocks in complex geological settings. This study aims to determine the fluid evolution in Sibumasu block of Thailand in the context of structural deformation using a framework of texture-specific stable isotope sampling, controlled by field mapping and structural measurements. Structural measurements were taken and related rock samples were collected from two outcrops within the shear zone of the Three Pagoda Fault Zone (TPFZ). These meas-urements were then integrated via a combination of structural stereo plots, petrographic analyses and carbon-oxygen stable isotope determinations. Veins observed have wideranging orientations and show cross-cutting relationships. Vein orientations cluster into two groups: 1) sub-horizontal with NNW-SSE orienta-tions and 2) sub-vertical with ENE-WSW orientations. The cross-cutting relationships were validated by petrographic analysis. All veins are syntaxial and made up of different mineralogies (ferroan-calcite, calcite, dolomite and silica). Isotopes sampled from veins define three different data fields. These distinct isotope clusters relate to different vein orientations and ultimately are interpreted to be responses to different deformation events. Some of the isotopic signatures are consistent with established burial trend for the Indochina block of Thailand. Veins in clusters 1 and 2, are interpreted to have precipitated from fluids in a closed subsurface hydrological system where rock-fluid crossflows dominated. These earlier veins likely formed during deformation related to the Indosinian Orogeny. When all matrix porosity and permeability was obliterated in deep burial, fluid flow became confined to tectonic fractures. Veins in cluster 3 precipitated from hotter fluids in deep pressurised settings with no rock-fluid cross flow in the adjacent rock matrix. These fluids were probably derived from a deeper source. These cluster 3 veins have an isotope signature that may have formed in the early Palaeogene, concomitant with the Himalayan orogeny as India commenced docking with Asia. This created hot fluid crossflows in fracture sets created by transpressional deformation along the Three Pagodas fault.